The impact of a training program for cascade relaxation on the performance of the individual back-air cycle junior gymnasts (10-11 years old) - Ahmed, G.; Mohammed, M.; Ibrahim, H. (Sports Science and Health, 2023)
This study presents one of the modern techniques in the field of cognitive psychology and completes the training process for artistic gymnastics coaches, in order to develop the performance level of artistic gymnastics juniors. The study included two homogeneous and equal groups, one experimental and the other controlled. The two researchers applied the training program for cascade relaxation accompanying the skill training to the experimental sample consisting of (8) young gymnasts to know the impact of this type of training in developing the skill level of the individual back somersault, while the control group underwent skills training only, and the duration of the program was limited to (08) weeks at (03) training units per week, the duration of each unit is (15) minutes. Findings showed that there is a positive direct correlation between the development of the relaxation ability level and the skill level of the back somersault straight for young gymnasts.